Memorial heritage and social memory of youth of Eurasian integration countries - Osadchaya, Galina Ivanovna (2021)
Based on the results of a sociological study, the article attempts a narrative explication of the attitudes of young people in Armenia, Belarus, Kazakhstan, Kyrgyzstan, Moldova, Tajikistan, and Russia toward their shared memorial heritage in the context of the permanent reinterpretation of the Soviet past in the former Soviet republics which appears important in the context of the ongoing search for new forms of economic and political integration in the Eurasian space. The study allows providing a characteristic of the place of the Soviet memorial heritage, especially that dedicated to the participation of the USSR in World War II, in the social memory of young people as a unifying factor of millennial and post-millennial generations of the former Soviet republics – participants in Eurasian integration which can contribute to the successful implementation of integration projects in the post-Soviet space. The post-memory generation is generally in favor of preserving the Soviet toponymic names of city streets and squares but young people in countries with a greater degree of linguistic and ethnocultural differences support renaming practices more often. At the same time, the authors note the ambivalence of young people’s attitudes towards the future of memorialization policies in their countries which preserves the possibility of potential revision and reconsideration of the Soviet past in the future.